Correlation Between Nutritional Deficiencies (E.G., Iron, Zinc) And Lymph Node Cytology Patterns: Study In Hilly Area Of Uttarakhand - Pandey, Deepika; Pradhan, Mohit; Mishra, Shubham; Tiwari, Kshama (Journal of Neonatal Surgery, 2025)
Background: Micronutrient deficiencies, particularly of iron and zinc, are prevalent in resource-limited regions and have known effects on immune function. This study aimed to evaluate the correlation between nutritional deficiencies and cytological patterns observed in lymph node aspirates from patients in the hilly region of Uttarakhand. Materials and Methods: This cross-sectional study included 234 patients with peripheral lymphadenopathy who underwent fine-needle aspiration cytology (FNAC) and serum nutritional assessment. Cytological patterns were classified as reactive hyperplasia, granulomatous lymphadenitis, suppurative inflammation, or neoplastic. Serum iron and zinc levels were measured, and associations between deficiencies and cytological patterns were analyzed statistically. Results: Iron deficiency was present in 53.8% of patients, zinc deficiency in 44.4%, and both deficiencies in 30.8%. Reactive lymphoid hyperplasia (41.9%) and granulomatous lymphadenitis (33.8%) were the most common cytological findings. A statistically significant correlation was found between iron deficiency and reactive lymphoid hyperplasia (p < 0.01), while no significant correlation was observed for zinc deficiency with specific patterns, though a higher frequency of granulomatous changes was noted in zinc-deficient individuals. Conclusion: Iron and zinc deficiencies are common among patients with lymphadenopathy in hilly regions. Iron deficiency is significantly associated with reactive lymphoid hyperplasia, suggesting an immune-modulatory influence on cytological response. Nutritional profiling may enhance diagnostic interpretation and guide holistic patient management in endemic and underserved populations